2020
DOI: 10.1093/ndt/gfaa142.p1328
|View full text |Cite
|
Sign up to set email alerts
|

P1328effectiveness of Music for Alleviating Pain During Haemodialysis Access Cannulation: A Multi-Facility, Single-Blind, Randomised Controlled Trial

Abstract: Background and Aims Repeated needle pain during haemodialysis (HD) access cannulations is a serious problem for HD patients. Although the efficacy of music for alleviating pain and anxiety is well established, there is insufficient scientific evidence related to its effectiveness in alleviating pain during access cannulations during HD. This study aimed to investigate the effects of music on reducing pain during access cannulating in HD patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Only three studies, Ikenoue et al , 40 Momenabadi et al 47 and Kishida et al 61 reported treatment costs ( online supplemental table 5 ). Ikenoue et al 40 compared music medicine (researcher selected) versus sounds without linguistic meaning, whereas Kishida et al 61 compared music medicine (researcher selected) versus sounds with linguistic meaning. Both studies used free online music; only tablet computers and headphones/earphones purchased for research purposes were used for sound reproduction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only three studies, Ikenoue et al , 40 Momenabadi et al 47 and Kishida et al 61 reported treatment costs ( online supplemental table 5 ). Ikenoue et al 40 compared music medicine (researcher selected) versus sounds without linguistic meaning, whereas Kishida et al 61 compared music medicine (researcher selected) versus sounds with linguistic meaning. Both studies used free online music; only tablet computers and headphones/earphones purchased for research purposes were used for sound reproduction.…”
Section: Resultsmentioning
confidence: 99%
“…29 Thus, we obtained 101 full texts and identified 38 eligible full texts reporting on 27 RCTs. 22 23 30-63 We denote each study by the author's name and year of publication: Aydin 2017, 30 Tapar 2017, 31 Aghbolagh 2020, 22 Arts 1994, 23 Balan 2009, 32 Çelikol 2019, 33 Schaal 2021, 34 35 Jacobson 1999, 36 37 Hsieh 2017, 38 Karaca 2022, 39 Ikenoue 2020, [40][41][42] Shabandokht-Zarmi 2017, 43 44 Hoseini 2019, 45 46 Momenabadi 2021, 47 Raghibi 2018, 48 Mou 2020, 49 Hartling 2013, 50 51 Jacquier 2022 (52-54)(44, 50, 59), Gerçeker 2019, 55 Nouira 2020, 56 Sahiner 2016, 57 Shahabi 2007, 58 Press 2013, 59 Zengin 2013, 60 Kishida 2019, 61 Fleckenstein 2022 62 and Alemdar 2023. 63 The detailed characteristics of the studies included in this review are presented in online supplemental tables 5 and 6.…”
Section: Study Selection and Trial Populationmentioning
confidence: 99%